MR microscopy to assess clot composition following mechanical thrombectomy predicts recanalization and clinical outcome: original research - Karimian-Jazi, Kianush; Vollherbst, Dominik; Schwarz, Daniel; Fischer, Manuel; Schregel, Katharina; Bauer, Gregor; Kocharyan, Anna; Sturm, Volker Jörg Friedrich; Neuberger, Ulf; Jesser, Jessica; Herweh, Christian; Ulfert, Christian; et al. (Journal of neuroInterventional surgery, 2023)
Background Mechanical thrombectomy (MT) is the standard of care for patients with a stroke and large vessel occlusion. Clot composition is not routinely assessed in clinical practice as no specific diagnostic value is attributed to it, and MT is performed in a standardized ‘non-personalized’ approach. Whether different clot compositions are associated with intrinsic likelihoods of recanalization success or treatment outcome is unknown. - Methods We performed a prospective, non-randomized, single-center study and analyzed the clot composition in 60 consecutive patients with ischemic stroke undergoing MT. Clots were assessed by ex vivo multiparametric MRI at 9.4 T (MR microscopy), cone beam CT, and histopathology. Clot imaging was correlated with preinterventional CT and clinical data. - Results MR microscopy showed red blood cell (RBC)-rich (21.7%), platelet-rich (white,38.3%) or mixed clots (40.0%) as distinct morphological entities, and MR microscopy had high accuracy of 95.4% to differentiate clots. Clot composition could be further stratified on preinterventional non-contrast head CT by quantification of the hyperdense artery sign. During MT, white clots required more passes to achieve final recanalization and were not amenable to contact aspiration compared with mixed and RBC-rich clots (maneuvers: 4.7 vs 3.1 and 1.2 passes, P<0.05 and P<0.001, respectively), whereas RBC-rich clots showed higher probability of first pass recanalization (76.9%) compared with white clots (17.4%). White clots were associated with poorer clinical outcome at discharge and 90 days after MT. - Conclusion Our study introduces MR microscopy to show that the hyperdense artery sign or MR relaxometry could guide interventional strategy. This could enable a personalized treatment approach to improve outcome of patients undergoing MT.
Zu diesem Artikel gibt es Supplementary Material (2 Seiten)
Gesehen am 15.02.2024